Aplicaciones tecnológicas de la rebanadora industrial de alimentos en procesos de transformación agroindustrial. - Moromenacho Rivera, Andrea Nicole (2023)
The aim this project is to develop a manual for the operation, maintenance and technological application from industrial food slicer in the research laboratory from Agroindustry Career, in order to strengthen the experimental learning the students, teachers and researchers from Cotopaxi Technical University. During the research, it focused on knowing the maintenance and operations correct use from slicer industrial food. Each manual contains a brief detailed description the operation, its components, general provisions, the steps, which must be followed for its correct operation and maintenance types, so that the equipment works correctly and prolongs its useful life, as well as the security measures, that must be performed responsible staff (students and teachers). It was made demonstrative pedagogical practices based on the organic white carrot chips elaboration with chicken flavoring, it was demonstrated, what with 53%, it has a very good acceptability for consumption, cassava sticks chips with spicy paprika flavoring, it has that with 47 %, there is a very good acceptability and radish chips with natural lemon flavoring that with 47%, it has a good collection for consumption, where it was got effective results. For getting the expressed results, they were made a tasting with 15 people, with the organoleptic analysis help, it was verified, what the organic chips managed to have excellent results with an acceptability 100% very good, thus fully complying with all the set aims by this integrator project.